Aplikasi Model Pertumbuhan Logistik untuk Estimasi Jumlah Penduduk Kabupaten Ponorogo - Nabila Asyiqotur Rohmah (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Population growth is a critical issue for government planning, necessitating accurate projections for future years to inform long-term policy decisions. This study explores estimating the population of Ponorogo Regency through a logistic growth model. The model’s differential equation, structured as a separable differential equation, was solved and applied to real population data to derive a specific solution. The results indicate that, among five tested models, four logistic growth models are viable for projecting the population of Ponorogo Regency.